Retrospective analysis of population-based causes of death and life expectancy in urban Western China from 2003 to 2012 - Deng Shi-min; Rong Shun-kang; Yao Yuan-qing; Qian Jun; Huang Jing; Li Nan; Zhou Ren-jiang (BMC, 2016)
Abstract Background Hitherto, a population-based analysis of the cause of death in urban areas of Western China has not been undertaken over an extended period. The aims of this study were to calculate the overall and annual cause-specific mortality rates by age and sex in urban areas of Western China from 2003 to 2012 and to evaluate the quality of the data. Methods We used Excel software, cause-of-death registrations, and International Classification of Diseases, 10th revision, codes to calculate the overall and yearly cause-specific crude mortality rates by age and sex, the Chinese age-standardized mortality rate, and life expectancies. Results In the Jiulongpo District from 2003 to 2012, there was an increase in the number of death case reports in the census-registered population, a decrease in the number of omitted deaths, and rise in the crude mortality rate. Except for 2003, the Chinese age-standardized mortality rate was the lowest in 2012 (330.83/100,000) and highest in 2005 (390.08/100,000). Life expectancy increased from 78.36 years in 2005 to 81.67 years in 2012. Conclusions With the development of its social economy, the Chinese government and public attach greater importance to cause-of-death surveillance. The quality of cause-of-death registrations has gradually increased, crude mortality rates have risen, the Chinese age-standardized mortality rate has fallen, and life expectancies have increased.